2020
DOI: 10.1007/s11255-020-02495-x
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between sclerostin and carotid artery atherosclerosis in patients with stage 3–5 chronic kidney disease

Abstract: Purpose Sclerostin is an antagonist of the Wnt/β-catenin pathway. We previously reported that sclerostin is closely related to carotid artery atherosclerosis and long-term outcome in hemodialysis patients. The present study investigated the association between sclerostin, renal function, and carotid artery atherosclerosis in non-dialysis patients with stage 3-5 chronic kidney disease (CKD 3-5ND). Methods A total of 140 patients with CKD 3-5ND were enrolled in this cross-sectional study. The Chronic Kidney Dise… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 38 publications
0
6
0
Order By: Relevance
“…Fourteen studies examining the association between serum sclerostin concentration and arterial stiffness or atherosclerosis severity were identified. 48,[56][57][58][59][60][61][62][63][64][65][66][67][68] Twelve studies reported significant positive associations, 48,[56][57][58][59][60][61][62][63][64][65][66] while one study reported a negative association 67 and one study reported no association. 68 Higher serum sclerostin has been associated with coronary, carotid, and peripheral atherosclerosis.…”
Section: Human Blood Samplesmentioning
confidence: 99%
See 2 more Smart Citations
“…Fourteen studies examining the association between serum sclerostin concentration and arterial stiffness or atherosclerosis severity were identified. 48,[56][57][58][59][60][61][62][63][64][65][66][67][68] Twelve studies reported significant positive associations, 48,[56][57][58][59][60][61][62][63][64][65][66] while one study reported a negative association 67 and one study reported no association. 68 Higher serum sclerostin has been associated with coronary, carotid, and peripheral atherosclerosis.…”
Section: Human Blood Samplesmentioning
confidence: 99%
“…68 Higher serum sclerostin has been associated with coronary, carotid, and peripheral atherosclerosis. [56][57][58][59] In contrast, Milovanova et al 67 reported an inverse association of serum sclerostin concentration with symptoms of coronary heart disease (CHD) in patients with ESRF. Multiple studies have demonstrated a significant association between serum sclerostin concentration and higher arterial stiffness (Table 3).…”
Section: Human Blood Samplesmentioning
confidence: 99%
See 1 more Smart Citation
“…Our result was similar to that of other authors. Zhao B. et al 22 found 74.3% of patients with carotid atherosclerotic plaques in a study enrolled by 140 CKD patients (44.3% diabetes). Yu L. et al 23 conducted a study with 330 MHD patients with an average age was 63.43 years old, median hemodialysis duration was 69 months, 16.4% diabetes, and the presence of atherosclerosis was 57.3% (189 cases).…”
Section: Discussionmentioning
confidence: 99%
“…Morales-Santana et al observed that in subjects with diabetes type 2, sclerostin levels were strictly associated with increased carotid intima-media thickness ( p < 0.05), carotid plaques ( p < 0.01), and aortic calcification ( p < 0.01) [ 9 ]. Kirkpantur et al also proved that sclerostin levels correlated with carotid intima-media thickness in subjects undergoing hemodialysis [ 7 ], whereas Zhao et al proved this in subjects with CKD stage 3–5 [ 24 ]. In a similar study, Chen et al showed that sclerostin levels were not only linked with carotid artery atherosclerosis but also with all-cause deaths [ 25 ].…”
Section: Discussionmentioning
confidence: 99%